12 RULES FOR LIFE : An Antidote to Chaos - PETERSON, JORDAN (London Allen Lane, 2018)
Jordan Peterson's work as a clinical psychologist has reshaped the modern understanding of personality, and now he has become one of the world's most popular public thinkers, with his lectures on topics ranging from the Bible to romantic relationships drawing tens of millions of viewers. In an era of polarizing politics, echo chambers and trigger warnings, his startling message about the value of personal responsibility and the dangers of ideology has resonated around the world. In this book, he combines ancient wisdom with decades of experience to provide twelve profound and challenging principles for how to live a meaningful life, from setting your house in order before criticising others to comparing yourself to who you were yesterday, not someone else today. Gripping, thought-provoking and deeply rewarding, "12 Rules for Life" offers an antidote to the chaos in our lives- eternal truths applied to our modern problems.
Include Illustrations, End notes and Index
Keywords: Rules for Lifes